Territorial Concentration of Firms in the Chorotega Region: An Analysis Using Spatial Economics Techniques - Arias Ramírez, Rafael (2011)
This article results from the research project entitled Analysis of TerritorialCompetitiveness and Labor Market in the Chorotega region, which is part of the research program in regional Economics we have been conducting at the Institute of Research for Economic Sciences of the Universidad de Costa Rica (IICE) since the year 2005. In this study we apply a series of instruments of spatial economics to identify spatial location of enterprises within the Chorotega region and their degree ofspatial association (cluster). To achieve this objective we use some applications of the Geographic Information System (GIS) and the Exploratory Spatial Data Analysis (ESDA)